Pemanfaatan Sumber Pembelajaran Digital untuk Pengembangan Diri Guru dan Pembelajaran di SD - Isti Rokhiyah; Mestika Sekarwinahyu; Amalia Sapriati (Postgraduate, University of Mataram, 2023)
This study describes the science literacy of elementary school students who are taught using the science practical work method. The research was conducted on grade 4 and grade 5 students at six public and private elementary schools in South Tangerang City, Banten. Data collection was carried out using tests, observation sheets, student activity sheets, and questionnaires. The results showed that students had good understandings, good performance, high interest, and high self-confidence.Â Moreover, students indicated good scientific attitudes and positive attitudes towards science.Â The conclusion is that learning science using the science practical work method can provide elementary school students fourth grades and fifth grades showed science literacy characteristics.